2000
DOI: 10.1002/(sici)1438-9312(200004)102:4<266::aid-ejlt266>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the seed oils of some commercial cultivars of melon

Abstract: Proximate analysis of the seeds from three commercial melon cultivars (Honey Dew, Hy‐mark and Orange Flesh) showed high percentage of lipids (25.7—27.6%) and proteins (15.2—19.2%). The physico‐chemical properties of the hexane‐extracted oil from the seeds of these cultivars were determined. Gas chromatographic analysis of the oils showed the presence of almost all fatty acids starting from C6— C24 except that of C11 , C21 C23 , C18:2 being the principal fatty acid followed by C18:1 , C16:0 , and C18:0 fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Previous studies carried out mainly on melons grown in some developing countries confirmed the interest in melon seeds as a possible functional ingredient [ 3 , 4 , 5 ]. In this regard, the nutritional composition of melon-seed cultivars grown in different countries, including Egypt [ 6 ], Brazil [ 7 , 8 , 9 ], Tunisia [ 10 ], and China [ 11 ], was studied.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies carried out mainly on melons grown in some developing countries confirmed the interest in melon seeds as a possible functional ingredient [ 3 , 4 , 5 ]. In this regard, the nutritional composition of melon-seed cultivars grown in different countries, including Egypt [ 6 ], Brazil [ 7 , 8 , 9 ], Tunisia [ 10 ], and China [ 11 ], was studied.…”
Section: Introductionmentioning
confidence: 95%
“…Viscosity values ranged between 25.75 mPa (tomato seed oil) to 51.2 mPa (pumpkin seed oil). Hy-mark and honey Dew melon seed oils which had lower acid (1.15 and 1.32%) and peroxide values (1.61 and 3.14 meq/Kg) 5 . According to variance analyses results, viscosity, acidity and peroxide values of seed oils were found significantly at the p<0.01 level.…”
Section: Resultsmentioning
confidence: 99%
“…According to variance analyses, the seed differences were found significantly at the p<0.01 on drymatter, crude oil, crude protein, and p<0.05 on ash content of samples ( Table 1). The seeds from three commercial melon cultivars (Honey Dew, Hy-mark and Orange Flesh) showed high percentage of lipids (25.7-27.6 %) and proteins (15.2-19.2 %) 5 . At the same time, crude protein and ash contents of both seeds were determined as 55.4 and 39.4 % and 7.23 and 6.18 %, respectively 13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations